The impact of extralegal factors on perceived credibility of child victims of sexual assault - Voogt, Ashmyra (Psychology, crime & law, 2020)
The study examined the impact of victim age, victim gender, and perpetrator gender, across five domains of witness credibility: accuracy, believability, competency, reliability and truthfulness. The study also investigated which of these sub-constructs is the best predictor of guilt. 231 adult lay-people completed a survey measuring perceived credibility. Victim age emerged as having the most consistent effect, with the 5- and 10-year-old victims rated as more credible than the 15-year-old victim. Despite their legal incapacity to consent to sex, 15-year-old victims appear to be viewed as ‘quasi-adults’. Victims were rated as more accurate and truthful when the defendant was male compared to when the defendant was female. This may be due to the availability heuristic, as cases involving female defendants are less common. A significant main effect for victim gender was found for the competency sub-construct, such that males were rated as more competent than females. This result suggests that gendered attitudes and stereotypes may begin in childhood and extend to complainants of sexual assault. Main effects for accuracy and truthfulness, were qualified by three-way interaction effects. The five-factor model of perceived credibility accounted for 42% of variance in guilt perceptions, with truthfulness emerging as the strongest predictor of guilt.